It gives you wheels: the university-based accelerators in start-up ecosystems. (15th February 2022) - Greco, Fabio; Tregua, Marco
Many scholars have investigated the growing phenomenon of start-ups in the last decade from various angles; this paper aims to join the ongoing debate over university-based accelerators (UBAs) by addressing how they contribute to the development and growth of start-ups and to the viability of a start-up ecosystem. The review led to consider actors, geographical contexts, and resources as the three main drivers shaping a start-up ecosystem and the support UBAs offered to start-ups. A preliminary analysis on several start-up ecosystems around the world and two on-field studies led the research to show methodological, theoretical, and practical advances, as UBAs offer a hard-to-replicate combination of suitable conditions for start-up acceleration, due to prestige in the business context, the operationalisation of models and methods, and the setting up of a fertile ground for start-ups.